Comparative Study on Phytoplankton Community in Two Newly Dug Ponds in Institut Teknologi Sumatera - Hendry Wijayanti; Andy Darmawan (UIN Sunan Gunung Djati Bandung, 2020)
Phytoplankton community plays an important ecological role in the aquatic ecosystems as the primary producers and forms the fundament of the aquatic food chain for supporting the water community. Thus, the phytoplankton community structure is a good indicator of water quality due to its sensitiveness to environmental stresses. Two newly dug ponds in Institut Teknologi Sumatera may give an opportunity to study the early colonizing stages of various freshwater communities including phytoplankton. The study attempted to determine the composition and abundance of phytoplankton. Samples were collected from two ponds (A and C) in the reservoir water of Institut Teknologi Sumatera. The content of Phosphorus (P), Nitrogen (N), and Chlorophyll-a (algae biomass) were determined. Phytoplankton had higher diversity in Pond C than Pond A in the study period, in which a total of seven taxa were found, namely Bacillariophycea, Cyanophyceae, Chlorophyceae, Conjugatophyceae, Dinophyceae, Euglenophyceae, Gymnodiniaceae. The most species abundance of both ponds was Peridinium sp. and Trachelomonas sp. The Pond C had the highest mean value of the Shannon-Wiener diversity index. The Linear mixed-effect model showed that low turbidity will result in high phytoplankton diversity. The finding of this study suggests that higher phytoplankton diversity would achieve a natural carrying capacity, and thus would serves as an indicator of ecosystem health.